Preliminary Descriptive Statistics of the Taiwanese Registry of Epilepsy and Pregnancy for the First 2 Years - Tung-Yao Chang; Chi-Wan Lai; Hsiang-Yu Yu; Jenn-Jeih Hsu; Yang-Hsin Shih; Chih-Ping Chen (Elsevier, 2007)
Objective: To present the descriptive statistics of the Taiwanese Registry of Epilepsy and Pregnancy (TREP) for the first 2 years. Materials and Methods: The pregnancies were recruited from May 2004 to January 2006 with a data format compatible with the International Registry of Antiepileptic Drugs and Pregnancy (EURAP) by referral. The data were collected from either face-to-face interview, telephone interview, or chart review by a research nurse. Five questionnaires (A-E) were required for each pregnancy. The preliminary data for the first 2 years are presented with general descriptive statistics. Results: Until January 2006, 43 pregnancies have been registered. Questionnaire A was completed in 43 cases, questionnaire B completed in 40 cases, questionnaire C completed in 34 cases, questionnaire D completed in 27 cases, and questionnaire E in eight cases. Among the 39 pregnancies known to take antiepileptic drugs (AEDs) during pregnancy, 28 pregnancies took one AED, nine pregnancies took two AEDs, and two pregnancies took three AEDs. The most commonly used drug was carbamazepine (19/39, 48.72%). Among the 27 pregnancies, who had delivered, the cesarean section rate was 44.44% (12/27), the premature birth rate was 7.41% (2/27), and the fetal malformation rate was 3.7% (1/27). Conclusion: The preliminary data concluded the efforts of TREP for the first 2 years. Although it is still premature to project a trend out of current data, the registry is expected to provide critical information to local prenatal counseling and contribute further to the international EURAP database.